P12.14 Clinical descriptions of pcr positive early syphilis infections. (13th September 2015) - Towns, JM; Leslie, DE; Denham, I; Azzato, F; Fairley, CK; Chen, MY
Abstract : Background: Globally, syphilis remains a major and resurgent public health problem with high incidence rates in many settings, including among men who have sex with men (MSM). Left untreated, syphilis can lead to further transmission, morbidity and enhanced Human Immunodeficiency Virus (HIV) transmission. A primary chancre is classically described as an indurated single painless ulcer at the site of Treponema pallidum inoculation. However, recent clinical experience is that primary syphilis can present atypically, as multiple and/or painful ulcers with features suggestive of genital herpes. We aimed to describe serology and Treponema pallidum polymerase chain reaction (Tp PCR) positive lesions of primary syphilis in men, the rates of painful or multiple lesions, whether there was concurrent genital Herpes simplex virus (HSV) infection and whether concurrent HIV infection altered the presentation. Methods: Tp PCR positive results with confirmatory syphilis serology and HSV PCR results reported by VIDRL were identified and compared to MSHC medical records over a five-year period from 2010 to 2014. Results: 183 patients fulfilled the criteria of Tp PCR positive primary syphilis. Primary syphilis lesions were frequently painful (49.2%) or multiple (37.7%), and were infrequently associated with HSV (2.7%). Presentation was not significantly altered by HIV status. Anal lesions were more common in HIV positive men (34.2%) than in HIV negative men (11.6%). Syphilis reinfections were more common in HIV positive men (39.5%) than in HIV negative men (11.7%). Conclusion: Tp PCR is a useful tool to confirm syphilis as a cause of genital lesions and positivity may precede serological markers. Early syphilis lesions may be clinically misidentified as HSV infection if syphilis is not considered. Awareness of the clinical variability of primary syphilis lesions should be included in health promotion messages to the public and health care providers. Disclosure statement: There are no conflicts of interest.